O direito à informação pública no âmbito do poder legislativo: um estudo comparado das potencialidades e desafios dos portais dos parlamentos brasileiro e mexicano na concretização da transparência ativa - De la Rue, Letícia Almeida (2014)
This study aimed to examine the legal treatment of the right to public information in Brazil and Mexico, comparing the laws through the observation of the portals of the federal Legislative Power, checking the state of that matter in these countries to determine how the use of portals can contribute to active transparency. Based on the assumption that, in the context of informational society, there is a great potential in the use of ICT as a tool for spontaneous disclosure of information, enabling the effective exercise of accountability, it was verified the importance of analyzing how the portals of the federal Legislative Power are being used as an instrument for implementation of the Law of Access to Information. For such, it was chosen a comparative analysis with Mexico, seeking contributions to the discussion of this subject in Brazil, developing the following research problem: through comparative study of Brazilian and Mexican parliament portals, how is the state of matter of the implementation of the laws on the portals of the federal legislature of each country? From this analysis, to what extent can be verified that the use of portals can contribute to the accomplishment of active transparency, achieving accountability in a more complete and appropriate way, and enabling greater social control over the administrative, financial and budgetary management of federal Legislative Power? The theoretical framework was composed by the works of Guillermo O'Donnell and Antonio Enrique Perez-Luño, adding the concepts of network society and informational society developed by Manuel Castells. To answer the research problem, it was used a hypothetical deductive approach, and a combination between comparative and monographic method of procedure. Along with that, it was used the technique of research in documentary sources and the bibliographic research, performing in the end the analysis of the portals of Mexican s and Brazilian s Legislative Power, using a structured online form. With the analysis, it was found that Brazil showed greater effectiveness in the implementation of active transparency in the surveyed. It was also noticed that Mexican law is very advanced, however, the progressive legislation and lifetime factors - the key variables that led to the choice of Mexico - do not automatically convert to a better implementation of the law. It was concluded that the use of portals as a tool to actualize the active transparency has great potential in the sense of leading civil society to supervise and monitor the performance of public officials, increasing the degree of accountability and thus enabling the empowerment of social actors in democracy. However, the fact that information is available does not mean immediate appropriation by citizens, because in many cases the information is not disclosed in an updated, completed and affordable way, as well as the potential must be weighed against the issue of digital inclusion, and with the understanding that technology is nothing more than an instrument of democratization, but that its results will depend largely on the attitude that the state adopts in relation to information disclosure.